Minority within a minority: Shia community in Ukraine - Tahiiev, Akif (Penerbit Universiti Kebangsaan Malaysia, 2021)
Ukraine is one of the largest countries in Europe and there is a significant Muslim minority here, among which there are several Shia communities. Aspects of the life and activities of the Shia community in Ukraine are almost unexplored. Although at the same time a number of studies were devoted to the Shiite minorities of Western European countries, therefore in this paper, we examined the characteristics of the life of the Shia community in Ukraine and compared it with the characteristics of the Shia communities in Western Europe. Special attention was paid to the peculiarities of the mentality of the indigenous Shiites, represented by Azerbaijanis. The features of the institutionalization of the Shia communities of Ukraine, the features of conducting divine services and mourning events of Ashura were considered. After analyzing the above problems, we came to the conclusion that the Shiites of Ukraine are more passive, so we tried to identify the reasons for such passivity, among which the most important are the Soviet "atheistic" past; cultural, national and linguistic diversity of representatives of the Shiite minority of Ukraine, which prevents larger gatherings of Shiites from being held. We consider the article as a basis for further research in this region, therefore, the purpose of the study was to highlight all possible problematic aspects of the life of Shiite minorities in Ukraine.